The Evolution of Theodosius Dobzhansky : Essays on His Life and Thought in Russia and America. - Adams, Mark B. (Princeton legacy library., 2014)
This volume not only offers an intellectual biography of one of the most important biologists and social thinkers of the twentieth century but also illuminates the development of evolutionary studies in Russia and in the West. Theodosius Dobzhansky (1900-1975), a creator of the ""evolutionary synthesis"" and the author of its first modern statement, Genetics and the Origin of Species (1937), founded modern Western population genetics and wrote many popular books on such topics as human evolution, race and racism, equality, and human destiny. In this, the first book devoted to an anal